Students and Tutors’ Perceptions of the Use and Functioning of University Tutoring - Klug, María Antonella (2019)
This article aims to study the functioning and perceptions of students and tutors of the university tutoring system in a private university institute in the city of Rosario. An exploratory-descriptive study was used, wich included a case study design. The university tutoring functioning was analized from the tutors’ perspective (with semi-structured interviews) and the first-year students’ perceptions (with the application of a questionnaire). The results indicate that, for tutors, the listening skills, the need for training, and the teamwork capacity are important. With regard to the students, it was found that more than half do not know about the tutoring, and that those who know about it manifest to have received the information from teachers  and peers. Some of them consider that this space relates to the theoretical orientation and manifest preference toward the academic tutoring function, while others consider that tutoring enables them to carry out a comprehensive vision of university life.